JURIDICAL ANALYSIS OF DEFAULTS IN MORTGAGE BUYING AND BUYING WITH BUY BACK GUARANTEE FACILITIES REVIEWED FROM ISLAMIC LAW AND POSITIVE LAW (Case study of PT. Sinarwijaya Ekapratista Banjar Wijaya Project) - Kamilulloh, Farhan (HUKUMAH: Jurnal Hukum Islam, 2023)
Buy back guarantee is a guarantee made by the developer in the form of a statement letter, as long as the house certificate is in the settlement stage, which functions as an anticipation for the bank if the customer defaults. The aim of the research is to find out the working mechanism of the buy back guarantee until the bank makes a buy back guarantee claim to the developer as well as the rules for late fines for buy back claims. As well as in the view of Positive Law and Islamic Law. This research method uses qualitative. The results of this research are: The developer has criteria for potential working partners to be able to work together and make an agreement. Efforts that can be made by the developer before the bank asks to claim a buy back guarantee can be submitted. If various forms of warnings from the developer are not responded to by the customer then the bank can execute the guarantee by paying the fees specified. has been detailed by the bank. The solution provided by the developer to customers is to find a buyer who is able to replace the position of the defaulting customer at the bank so that they can carry out the transfer of rights to the unit. According to Islamic law, the imposition of late fines and penalty fees in the details issued by the bank can be reduced by the LTV of the developer's deposits which are still held in the bank. Settlement of the buy back guarantee between the developer and the customer can be resolved through non-litigation (outside of court). The developer pays the buy back guarantee according to the bank's request by reducing penalty fees and late fines distributed by the bank to Poscariti. Both the view of Islamic law and positive law allow it as long as no one is harmed.